ECOLOGICAL ENTREPRENEURSHIP AND INNOVATION IN WOOD: INSTITUTIONAL DIMENSION - Muryn, Roman (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
Ecological entrepreneurship in the field of wood use through the prism of an institutional approach is in the focus of the paper. The influence of formal and informal institutions on the formation of conditions for the implementation of innovations, resource-efficient technologies and the development of sustainable forest use is revealed. Particular attention is paid to innovations in the wood processing industry, in particular bioeconomy, circular production models and digitalization of processes. The main barriers to development are identified, including institutional instability, insufficient funding and limited interaction between market participants. The prospects for improving the institutional environment to increase the environmental and economic efficiency of the industry are substantiated. The importance of adaptation to European environmental standards in the context of sustainable development is considered.